The Atlantic Almanac. - Mitchell, Donald Grant, 1822-1908. (Tufts University. Tisch Library., 2018)
Contains 80 pages and 4 color plates. Essay and narrative content includes: Fireside, by the Editor; Round the World in a Hack, from Colonel Ingham's Papers; Roadside, by the Editor; the Song-Birds of North America, by Thomas M. Brewer; Brookside, by the Editor; Summer Rain by George Cooper; My Garden Acquaintance by James Russell Lowell; Side by Side, by the Editor; What Pictures Shall I Hang on my Walls?, by Harriet Beecher Stowe; the Middle States by Josiah Quincy; Talks Concerning the Human Body and its Management, by the Professor at the Breakfast-Table; the Risks and Failures of City Life, by Rev. Joseph P. Thompson, D.D., LL. D.; the Nineteenth Century by C.P. Cranch.